Impact of COVID-19-related regulatory changes on nationwide access to buprenorphine: An interrupted time series design - Payel Jhoom Roy; Katherine Callaway Kim; Katie Suda; Jing Luo; Xiaoming Wang; Donna Olejniczak; Jane M Liebschutz (Drug and Alcohol Dependence Reports, 2023)
Background: The impact of COVID-19-related healthcare changes on access to buprenorphine (BUP) nationwide in the US is unknown. Methods: We conducted an interrupted time series with the IQVIA LRx database. The study timeline included BUP prescriptions from 52 weeks before (2/23/19–2/21/20) to 52 weeks after (4/4/20–4/2/21) the initial pandemic period (2/22/20–4/3/20). Segmented regression estimated relative changes in total milligrams (MG) of BUP available per week nationwide at 1, 26, and 52 weeks post-initial-pandemic. We evaluated treatment disruptions in previously stable patients, defined as ≥6 months of BUP prescriptions. Results: A total of 31 617 849 prescriptions were included. Total MG BUP dispensed increased at 1 and 26 weeks and then returned to baseline trends at 52 weeks post-initial pandemic period (4.1% [95% CI: 3.7,4.5], 2.1% [1.5,2.6], 0.1% [-0.6,0.9]). Stably-treated patients saw a decrease in 7-, 14-, and 28-day treatment disruptions at 52 weeks post-initial-pandemic period (-21.6% [-25.6,-17.7]; -10.8% [-16.3,-5.3]; -27.3% [-33.0,-21.6]). Men retained an increase in MG BUP compared to women at 52 weeks (0.7% [0.01,1.4] versus -0.6% [-1.5,0.2]). Younger age groups (18–29 years and 30–39 years) had a decrease in MG BUP at 52 weeks compared to expected baseline trend (-16.6 [-24.2, -9.0]; -1.6 [-3.0, -0.1). Patients with Medicaid demonstrated an increase in MG BUP at 52 weeks (8.3% [6.3,10.3]). MG BUP prescribed by APP prescribing increased by over 140 000 mg per week prior to the pandemic and continued to increase. Conclusions: Regulatory changes around buprenorphine prescribing facilitated patient access to buprenorphine during the pandemic.